Knowledge of Financial Instruments and Financial Management for Sailing School Cadets - Ulfa Puspa Wanti Widodo; Wahyu Helmy Dimayanti Sukiswo; Rizdina Azmiyanti; Amir Mahmud; Nanda Wahyu Saputra (Future Science, 2023)
Indonesia, as the largest maritime country in the world, is currently racing to increase maritime transportation capacity, thereby creating quite a lot of job opportunities in the shipping sector. The seafaring profession with fantastic salaries attracts people who want their financial levels to be guaranteed. Problems often faced by seafarers include high levels of consumerism and a high lifestyle which can cause seafarers to experience poverty at the end of their productive years. This research aims to determine the extent of cadets' understanding of financial instruments and financial management, as well as to provide them with awareness of the importance of financial management. The dimensions used are financial literacy, financial attitudes, and financial management. This research used a sample of 33 cadets at the Bhakti Samudera Surabaya Shipping Vocational School and the data was analyzed using a descriptive qualitative approach. The research results concluded that the cadets had good financial literacy, were able to make planned financial decisions, and had sufficient financial management skills. Cadets have an awareness of financial planning and management, including in the form of investments in fixed assets and savings funds. Cadets can record their income and expenses so that financial management can be carried out optimally.